Analisa Pushover dan Eksperimen Struktur Portal dengan Dinding Batubata dengan Menggunakan Angkur pada Kolom dan Balok pada Non Engineered Building - Hutajulu, Marsaulina; Tarigan, Johannes; Tarigan, Perwira (Department of Civil Engineering, Diponegoro University, 2018)
Based on the findings in almost all earthquakes that hit Indonesia, buildings that were damaged and collapsed were simple non-engineered buildings. Where buildings are built based on practical experience without structural calculations. One form of damage to non-structural components and structures is the relationship between columns and brick walls, where cracks and separation between columns and walls occur due to lack of anchors (cuttings). To find out how much an earthquake load can make a test object that uses anchor has been destroyed, a pushover analysis is carried out numerically and experimentally. From the numerical results it is obtained a pushover of 7490 kg and a displacement of 16.7 mm, while the experimental results obtained a pushover 7,540 kg and 56.5 mm displacement. Numerical results and experiments are very close at 99.34%.